(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
Digital transformation is fundamentally reshaping the landscape of contemporary education, placing unprecedented demands on teachers’ professional capabilities. This study investigates the formation of acmeological competence among higher education teachers in Uzbekistan within the context of accelerating digitalization. Acmeological competence — the integration of peak professional achievement with continuous self-improvement — is examined through four interrelated components: motivational-value, cognitive-activity, reflective-evaluative, and creative-innovative. Employing a mixedmethods research design, data were collected from 180 teachers across three higher education institutions in Tashkent region (2022–2024) using the adapted Derkach acmeological diagnostics instrument and a DigComp 2.2-aligned digital competence scale. Results reveal a significant positive correlation (r = 0.67, p < 0.01) between digital competence and acmeological competence levels. Only 23% of participants demonstrated high or very high acmeological competence, while 68% reported insufficient readiness for technology-integrated teaching. A four-stage developmental model — Diagnosis, Training, Implementation, and Monitoring — is proposed and validated as an effective framework for systematically elevating teacher acmeological competence in digital environments. Findings contribute to the emerging field of digital acmeology and provide actionable guidance for educational administrators and policy makers.